Corn Value Chain in Dompu: Constraints and Alternative Policy Interventions to Improve the Value Chain - Muktasam Abdurrahman; Parta Tanaya I.G.L; Nurjannah S; Janet R (LPPM Universitas Mataram, 2022)
Even though corn has been a common agriculture commodity growing by Dompu farmers, few issues remain such as limited input supply especially fertilisers. As results, farmers could not follow the recomended fertiliser doses that lead to low productivity. This study was conducted to clearly identify the issues and constraints along the corn value chain, and identify options to address the issues. Quantitative and qualitative menthods were applied to the study. The findings from this study highlight that the corn value chain was very simple where farmers sell their corn to the village level collectors named as palele, then the palele sell the corn to the sub-district level collecotrs, and then they sell to the exporters. It is the roles of these exporters to sell the corn to other island and or to international markets. Issues found in the corn value chain are: the limited supply of fertilisers, broadcasting technique for fertilizer application, corn price fluctuation, and low corn productivity. It is recomended that the local government take few policy options to address the issues, and improve the value chain performance that lead to better smallholder farmers’ livelihood improvement.